Study on the Ecotoxic Effects of Uranium and Heavy Metal Elements in Soils of a Uranium Mining Area in Northern Guangdong - Zehui Zhang; Zhenping Tang; Yong Liu; Haiyang He; Zhixin Guo; Peng Feng; Liang Chen; Qinglin Sui (Toxics, 2023)
To investigate the heavy metal contamination of soil in a uranium mining area in northern Guangdong, a physicochemical evaluation method was used to evaluate the contaminated soil near the pit and tailings pond of the uranium mining area, determine its heavy metal content and evaluate its ecological risk using the Nemerow integrated contamination index, ground accumulation index and potential ecological risk index. The results show that the average content of nine heavy metal elements in the soil of the uranium mining area exceeds the background value of red soil in Guangdong Province. Three pollution evaluation indices all indicate that Cd, As and U have serious pollution and high ecological risk, while the remaining elements are weakly polluted and the potential ecological risk of the six sampling sites all show very strong risk. On this basis, soil ecotoxicity was evaluated using ostracods (Cypridopsis vidua and Heterocypris sp.), Vibrio fischeri and Vicia faba L. Higher concentrations of heavy metals at individual sites (T1, T2, P2) resulted in higher mortality of ostracods, higher inhibition of Vibrio fischeri luminescence and a significant reduction in germination and pigmentation of broad beans. The results of the biotoxicity evaluation were consistent with the results of the physicochemical evaluation, allowing for a more direct and comprehensive evaluation of the ecotoxic effects of uranium and heavy metals in the mine soils.